(untitled) (Experimental biology, 2018)
This paper presents the results of production testing immunogenicity of inactivated rabies virus vaccine developed in RIBSP agricultural and domestic animals. The inactivated rabies vaccine was prepared from the «VRC-RZ2» vaccine strain grown in BHK-21 culture cells, inactivated with β-propiolactone and adding aluminum hydroxide gel adjuvant. This work was conducted under the two farms of Almaty and Akmola oblasts of Kazakhstan. After 28 days of vaccination on serum of vaccinated animals was tested by neutralization with white mice. The studies under test vaccine was immunogenic for farm and domestic animals with induced formation of the vaccinated animals in the VNA titres of at least 3 log2. This VNA titer corresponds to the international standards required by the European Pharmacopoeia in the development of the rabies vaccines. Throughout the test the vaccine general condition of the animals was satisfactory, loss of appetite, depression, lethargy, excessive salivation were observed. Thus, the vaccine successfully passed production tests to determine the immunogenicity on domestic and farm animals, and was registered on the register of Kazakhstan veterinary preparations.